Patient Readiness for Remote Healthcare Services in the Context of the COVID-19 Pandemic: Evidence From European Countries - Borda, Marta; Grishchenko, Natalia; Kowalczyk-Rólczyńska, Patrycja (Frontiers in Public Health, 2022)
Despite the fact that remote services were successfully implemented in most European social and health systems before 2020, the COVID-19 pandemic has led to an unprecedented development of health and social care services provided in this form. This paper compares the readiness of patients to use the digital solutions in healthcare systems implemented in EU countries, in response to the current pandemic situation. In the study, technological, health insurance, and demographic variables were selected on the basis of substantive criteria. Next, the linear ordering method was applied to make a ranking of the analyzed countries according to the level of patients’ readiness to use digital healthcare services. The main findings show that the Netherlands and Ireland are characterized by the highest level of patients’ readiness for using remote healthcare services. On the other hand, Romania and Bulgaria are among the countries with the lowest readiness. The study also made it possible to group European countries according to the level of patients’ preparedness.